The moorchild - McGraw, Eloise Jarvis (New York : Margaret K. McElderry Books, 2007)
Feeling that she is neither fully human nor "Folk," a changeling learns her true identity and attempts to find the human child whose place she has been given.
Includes a reading guide and suggestions for related activities.
Newbery Medal Honor Book, 1997.
Keywords: Changelings -- Fiction; Fairies -- Fiction; Identity -- Fiction